the impact of work feedback on work engagement: evidence from the jordanian faculty members - HANSON, ROBERT J.; TAQATQA, MANAL RASHID (The journal of contemporary issues in business and government, 2021)
This study examined the impact of work feedback on work engagement of faculty members at Jordanian private universities. The increased turnover and burnout among Jordanian faculty members was the reason for examining such relationship. A quantitative correlational survey design research method was used to collect data from 112 faculty members who are currently employed at Jordanian private universities utilizing Job Demands-Resources (JD-R) model and Utrecht Work Engagement Scale (UWES-9) model. Descriptive statistics and correlational frequency were used to answer the research question related to the relationship between the job resources indicators of work feedback, and work engagement. Participants were Jordanian faculty members who are involved in classroom teaching and holders of masters or doctoral degrees. The P-Value was found at a significant level of .000 for each of work feedback on the level of work engagement of faculty members. It was found that by providing work feedback practitioners at Jordanian private universities might increase their faculty members’ level of work engagement and decrease turnover and burnout. Future research recommendations made were to encourage researchers to explore ways that might assist university administrators on improving their techniques and skills related to work feedback to their faculty members.